Direct visualization of chimeric antigen receptors on primary human T cells using dSTORM super-resolution microscopy - Gehrke, Leon; Seifert, Nicole; Spieler, Peter; Verbruggen, Christina; Seifert, Rick; Toppeta, Fabio; Krick, Maximilian; Doose, Sören; Einsele, Hermann; Hudecek, Michael; Sauer, Markus; Nerreter, Thomas (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR) T cells are a transformative treatment for hematological malignancies, and concerted efforts in the field are aiming to translate this success to solid tumors and autoimmune diseases. There is a desire in the field to accurately assess CAR organization and spatiotemporal expression to elucidate mechanistic details of CAR-T cell mediated anti-tumor activity and enable evaluation of the potency and safety of CAR-T cell products. We applied an IgG4-targeted F(ab)2 to achieve direct CAR labeling for super-resolution microscopy by direct stochastic optical reconstruction microscopy (dSTORM). This enabled us to determine CAR surface expression on human primary T cells with single-molecule resolution independent of CAR specificity. We combined this direct CAR detection approach with a phenotypic assessment of the CAR-T cells, highlighting prospective applications to gain detailed mechanistic insights. With this new approach, we were able to detect the surface expression of CARs targeting SLAMF7, BCMA and CD19 with minimal background. We determined T cell subtype, donor material, and CAR construct as contributing factors shaping CAR surface expression and identified putative influence of CAR surface expression on CAR-T cell activation state. Here we provide a novel, tag-free approach to gain insights into the surface expression of CARs, illustrating the potential of super-resolution microscopy to inform the application of synthetic immune receptors for CAR-T cell therapy, potentially building the basis for more intricate and combinatorial studies to further improve the efficacy of CAR-T cell immunotherapy, predict therapeutic outcome and ensure optimal care for patients.